Mechanical and microstructural effects of varying welding currents in GTAW of 7075-T62 aluminum - Septianissa, Selly; Hadining, Wanidya Ni’immallaili; Chandrasari, Ayu Zahra (Jurnal Polimesin, 2025)
Aircraft structures require diverse joining techniques, including riveting, bolting, bonding, and welding. While welding is less common in aerospace manufacturing due to concerns about the thermal sensitivity of aluminum alloys, it offers potential advantages such as weight reduction and the elimination of mechanical fasteners. This study investigates the effect of welding current on the microstructure and mechanical properties of 7075-T62 aluminum alloy welded using Gas Tungsten Arc Welding (GTAW) with ER 4043 filler metal. Welding currents of 40 A, 50 A, and 60 A were examined to assess their influence on tensile strength, hardness, and weld integrity. Results indicate that 50 A produces the highest tensile strength (34.297 kgf/mm²) and hardness (74.8 HRB), whereas 40 A results in lower tensile strength (26.471 kgf/mm²) and hardness (71.7 HRB). At 60 A, excessive heat input leads to increased porosity and deeper penetration, causing microstructural defects. The findings underscore the importance of optimizing welding parameters to balance mechanical performance and minimize defects. This study provides insights that are particularly relevant to aerospace applications, where reliable and high-strength welded joints are critical.